2012
DOI: 10.1089/thy.2011.0290
|View full text |Cite
|
Sign up to set email alerts
|

Propylthiouracil Increases Sodium/Iodide Symporter Gene Expression and Iodide Uptake in Rat Thyroid Cells in the Absence of TSH

Abstract: Background: Propylthiouracil (PTU) and methimazole (MMI) are drugs that are widely used to treat Graves' disease. Although both exert an antithyroid effect primarily by blocking thyroid peroxidase activity, their molecular structure and other actions are different. We hypothesized that PTU and MMI may have differential effects on thyroid-specific gene expression and function. Methods: The effects of PTU and MMI on thyroid-specific gene expression and function were examined in rat thyroid FRTL-5 cells using DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Fumarola et al (2010) stated that PTU inhibits iodine oxidation and monodotyrosine ionization. It is also prevented the coupling stage and inhibited the peripheral conversion of (T4) to (T3).So, it suppresses the synthesis of thyroid hormones by blocking the activity of thyroid peroxidase (Sue et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Fumarola et al (2010) stated that PTU inhibits iodine oxidation and monodotyrosine ionization. It is also prevented the coupling stage and inhibited the peripheral conversion of (T4) to (T3).So, it suppresses the synthesis of thyroid hormones by blocking the activity of thyroid peroxidase (Sue et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…As described before [10], the absorption of 131I absorption by the thyroid gland increases during the rebound effect and is probably connected to the NIS expression increase after administration of KI [2] and PTU [15]. This phenomenon is a reaction to the thyroid gland blockade and the change of iodine content in the thyroid gland.…”
Section: Resultsmentioning
confidence: 62%
“…In general, it is considered that the thyroid gland saturates with iodine within one week and then saturation blocks further absorption of iodine. M. Sue confirmed this premise [15], by determining that PTU causes the expression of the sodium iodide symporter (NIS) to increase in thyrocytes in absence of the thyroid-stimulating hormone (TSH). In a previous study using EPMA under iodineinduced thyroid blockade, we found that the expression of NIS in the thyroid gland increased during the first 5 days of the blockade, along with a decrease of intrathyroidal iodine [2].…”
Section: Introductionmentioning
confidence: 90%
“…And we found there were no obvious toxic effects of methimazole on the astrocytes (Figure 1(a)). Thereafter, 5 mM was used for the following study in the scratch wound model based on the cell viability result and a previous report on a cell culture model [19]. Next, we tested our primary hypothesis whether methimazole could inhibit the upregulation of the GFAP protein in a scratched astrocyte culture.…”
Section: Resultsmentioning
confidence: 99%
“…Methimazole was purchased from Sigma and dissolved in DMEM. The doses used in the study were referred from the previous publication [19]. Animal protocols were approved by the Experimental Animal Ethics Committee of China-Japan Union Hospital, Jilin University, Jilin Province, China.…”
Section: Methodsmentioning
confidence: 99%